Tata Kelola Dalam Penyaluran Bantuan Pangan Non Tunai (BPNT) Di Kelurahan Gembor Kota Tangerang - Wike Oktapiani (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
Good governance is something related to actions or behavior that are directing, controlling or influencing public affairs to realize these values in everyday life. The purpose of this study is to determine the process of distributing Non-Cash Food Assistance (BPNT) in Gembor Village, To determine the effectiveness of the distribution of Non-Cash Food Assistance (BPNT) in Gembor Village, To determine the inhibiting factors and factors driving the success of the Non-Cash Food Assistance (BPNT) program. To find out how to overcome the inhibiting factors in the Non-Cash Food Assistance (BPNT) program. This study used descriptive qualitative methods and involved informants from the Gembor Village apparatus, BPNT officers and BPNT recipient communities. In this study using the Van Doeveren theory with its five principles, namely (1) Accountability, (2) Effectiveness and efficiency, (3) Openness and Transparency, (4) Participation, (5) rule of law. The results of this study with the five principles of Van Doeveren that have been implemented properly only the principles of Accountability and the principles of Effectiveness and efficiency, while the principles of Openness and Transparency, Participation, the Rule of Law have not been implemented properly.Keywords: governance, non-cash food assistance (BPNT).